A subset of extracellular vesicles carries the bulk of microRNAs in commercial dairy cow's milk. Issue 1 (1st December 2017) - Benmoussa, Abderrahim; Ly, Sophia; Shan, Si Ting; Laugier, Jonathan; Boilard, Eric; Gilbert, Caroline; Provost, Patrick
ABSTRACT: MicroRNAs are small gene-regulatory RNAs that are found in various biological fluids, including milk, where they are often contained inside extracellular vesicles (EVs), like exosomes. In a previous study, we reported that commercial dairy cow's milk microRNAs resisted simulated digestion and were not exclusively associated with canonical exosomes. Here, we report the characterization of a milk EV subset that sediments at lower ultracentrifugation speeds and that contains the bulk of microRNAs. Milk EVs were isolated by differential ultracentrifugation and Iodixanol density gradient (IDG), and analysed for (1) microRNA enrichment by reverse transcription and quantitative polymerase chain reaction (RT-qPCR), and (2) EV-associated proteins by Western blot. Milk EVs were characterized further by dynamic light scattering (DLS), density measurements, fluorescent DiR and RNA labelling, high-sensitivity flow cytometry (HS-FCM), transmission electron microscopy (TEM), proteinase K and RNase A assay, and liquid chromatography tandem-mass spectrometry (LC-MS/MS). We found that the bulk of milk microRNAs (e.g., bta-miR-125b, bta-miR-148a, etc.) sediment at 12, 000 g and 35, 000 g . Their distribution pattern was different from that of exosome-enriched proteins, but similar to that of several proteins commonly found in milk fat globule membranes (MFGM), including xanthine dehydrogenase (XDH). These low-speed ultracentrifugation pellets contained cytoplasm-enclosing phospholipid bilayered membrane vesicles of a density comprised between 1.11 and 1.14 g/mL in Iodixanol. This milk EV subset of 100 nm in diameter/ 200 nm hydrodynamic size resisted to proteinase K digestion and protected their microRNA content from RNase A digestion. Our results support the existence of a milk EV subset pelleting at low ultracentrifugations speeds, with a protein coating comparable with MFGM, which contains and protects the bulk of milk microRNAs from degradation. This milk EV subset may represent a new EV population of interest, whose content in microRNAs and proteins supports its potential bioactivity.